2014
DOI: 10.1039/c4cc04381b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the catalytic asymmetric 1,3-dipolar cycloaddition of azomethine ylides

Abstract: Catalytic asymmetric 1,3-dipolar cycloadditions of azomethine ylides have turned out to be one of the most efficient methods for the preparation of enantioenriched pyrrolidines. The past decade has witnessed the development of a bunch of well-defined catalytic systems capable of affording excellent diastereo and enantioselectivities. Recently, a great effort has been focused on expanding the scope of the cycloaddition with regard to both reaction partners. In this review,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 352 publications
(90 citation statements)
references
References 117 publications
0
89
0
1
Order By: Relevance
“…14 Over the past few decades, some examples of the asymmetric 1,3-dipolar cycloaddition of azomethine ylides with dipolarophiles catalysed by chiral metal complexes and organocatalysts have been reported with excellent levels of stereoselectivity. 15 In particular, Hou et al 16a first reported switchable exo/endo selectivity in the 1,3-dipolar cycloaddition reaction of azomethine ylides with nitroalkenes. Later, Arai reported on the use of a PyBidineCu(OTf) 2 catalyst to synthesise endo-selective pyrrolidine products.…”
Section: Catalytic Asymmetric 13-dipolar Cycloadditionmentioning
confidence: 99%
“…14 Over the past few decades, some examples of the asymmetric 1,3-dipolar cycloaddition of azomethine ylides with dipolarophiles catalysed by chiral metal complexes and organocatalysts have been reported with excellent levels of stereoselectivity. 15 In particular, Hou et al 16a first reported switchable exo/endo selectivity in the 1,3-dipolar cycloaddition reaction of azomethine ylides with nitroalkenes. Later, Arai reported on the use of a PyBidineCu(OTf) 2 catalyst to synthesise endo-selective pyrrolidine products.…”
Section: Catalytic Asymmetric 13-dipolar Cycloadditionmentioning
confidence: 99%
“…Others are relatively unstable and must be prepared in situ. Several recent reviews have focused on these increasingly popular reactions [18,[70][71][72]. Theoretical analyses have given significant insights into the controlling features of 1,3-dipolar cycloaddition reactions [73].…”
Section: Dipolar Cycloaddition Reactionsmentioning
confidence: 99%
“…[3] One of the most powerful approaches for the preparation of pyrrolidines is the 1,3-dipolar cycloaddition of azomethine ylides with activated olefins. [4] Over the course of the past decade, a great effort has been devoted to the development of catalytic systems based either on the use of different metal salts and chiral ligands [5] or organocatalysts. [6] With this set of outstanding systems, much interest has been recently devoted to expanding the scope of the cycloaddition to a wider variety of dipoles and dipolarophiles.…”
Section: Introductionmentioning
confidence: 99%